PENGARUH RESESI GLOBAL TERHADAP PERGERAKAN HARGA SAHAM DI INDONESIA TAHUN 2023 - Pratiwi, Sophia; B, Idwal; Yustati, Herlina (ITB AAS Indonesia Surakarta, 2024)
The aim of this research is to find out how the global recession will affect stock price movements in Indonesia in 2023. The research method used is quantitative with secondary data collection techniques in the form of inflation, exchange rate and interest rate data. The data analysis technique used is multiple linear regression using the SPSS version 25 program. The results of the research show that the variables inflation, interest rates and exchange rates influence stock price movements by 17.9%. First, there is no significant influence of inflation (X1) on JII share price movements, second, there is a negative influence of interest rates (X2) on JII share price movements, third, there is no influence of the exchange rate on JII share price movements. while the rest is influenced by other variables not studied.